EFEKTIVITAS PEMBERIAN KAPSUL IODIUM DOSIS TINGGI TERHADAP STATUS IODIUM WANITA USIA SUBUR (WUS) YANG MENGKONSUMSI BAHAN MAKANAN SUMBER SIANIDA TINGGI - Saidin, M.; S., Sukati; K., Suryati; Kristanto, Dhoni; Samsudin, Samsudin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
THE EFFECTIVENESS OF ORAL HIGH DOSE IODINE SUPPLEMENTATION TO IODINE STATUS OF CHILDBEARING AGE WOMEN CONSUMING OF FOOD HIGH IN CYANIDE CONTENT. Background: It was reported by Iodine Deficiency Disorder Research Institute of Ministry of Health that prevalence of childbearing age women (CBAW) with abnormal of serum Thyroid Stimulating Hormone (TSH) value in Magelang district was around 23%, while Urine Iodine Excretion (UIE) considered normal (112 πg/L). The average of cyanide content of daily food consumed was 29.4 mg/day. These findings indicated that there was a relationship between cyanide consumed and Iodine Deficiency Disorder (IDD). As one of goitrogenic agents, cyanide inhibited Iodide (I) entering into thyroid cells, further more disturbed process of thyroid hormone (T4 and TSH) synthesis. Objectives: To investigate the effect of the supplementation of high dose Iodine by oral (capsules) to iodine status of childbearing age women consuming foods high cyanide in IDD endemic area. Methods: The study design was "intervention with quasi experiment trial". The study sites covered two sub-district, namely Srumbung and Salam sub-district of Magelang district of Central Java. A total of 80 CBAW (19-45 years old) consuming high intake of cyanide were randomly taken as treatment group and another 80 CBAW with low intake of cyanide as control group. Data collection was conducted before and after supplementation of iodine capsules (200 mg). Each subject received two capsules and was evaluated 6 months later. Data collected were cyanide content of daily food consumed, serum TSH, urine thiocyanate and urine iodine excretion as well. Results: The baseline data showed that no significant difference In the UIE between group I (CBAW high intake of cyanide) (99 ng/L) and group II, those of consuming low intake of cyanide (103.5 ng/L). After one month intervention the UIE of both groups increased significantly, group I = 311 ng/L and group II = 339 ng/L. After 6 months intervention the UIE of both groups still considered high, group I= 291 ng/L and group II = 315 ng/L. The proportion of CBAW with low status of iodine (based on TSH value > 5 nJ/L) for group I decreased to 6.3%, while for group II no changes. The effectiveness of high dose iodine supplementation to iodine status of CBAW with high intake of cyanide was slightly lower than those with low intake of cyanide (70 vs 100). Conclusions: Neither difference effect of high dose iodine supplementation to iodine status of childbearing age women with high intake of cyanide nor to those with low intake of cyanide. Keywords: effectiveness, high dose, supplementation, iodine status, childbearing age women, cyanide, Urine Iodine Excretion, thyroid hormone.